Outcomes in Sequential Intragastric Balloon Treatment for Patients With Super Obesity - A Single Centre Retrospective Analysis - Felix Hammett; Mariam Asarbakhsh; Hussamin Adwan; Arin Saha; Robert Adair; Mark Peter; Brian Dobbins; William Ainslie; Tamir Salih (Journal of Obesity Management, 2024)
Objective We aimed to assess outcomes in patients undergoing sequential intragastric balloon (IGB) treatment for obesity. Methods Consecutive patients who underwent treatment between May 2014 and February 2023 were identified. We recorded outcomes including: weight at 3-monthly intervals, progression to definitive bariatric procedure and morbidity. Results 45 patients were identified. Median weight loss with first IGB was 15.2kg (8.8%). 11 patients (26.7%) had a second IGB, with median weight loss of 3.3kg (1.9%). 21 patients (46.7%) were suitable for definitive surgery after first IGB treatment. One further patient (2.2%) was suitable for surgery after a second IGB. During first IGB, median weight loss was observed during the each of the first three quartiles (months 0-3: 10.1kg; months 3-6: 2.3kg; months 6-9: 4.2kg). There was a median 2kg weight gain during months 9-12. Conclusions Greatest weight loss was achieved during first IGB treatment. Sequential IGB treatment did not lead to beneficial weight loss or progression to surgery. Weight loss with first IGB was not uniform across the 12 month period of treatment, with net weight gain during the last quartile.
Keywords: Intragastric